Pengaruh Earned Media Dan Sosial Media Terhadap Peningkatan Penyewa Pada Usaha Rental Norma Rent - Salinding, Erlina; Mince Batara; Jens Batara Marewa (Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this research is to determine the influence of Earned Media and Social Media on increasing Norma Rent rental rents. The type of research used in this research is quantitative research. The research results of this study are that Earned media has a positive and significant effect on increasing rent in the Norma Rent rental business with a Tcount value of 9.737 > Ttable 2.052 with a significant value of 0.000 <0.05, so H1 is accepted. Social Media has a positive and significant effect on increasing rent in the Norma Rent rental business with a Tcount value of 2.444 > Ttable 2.052 with a significant value of 0.021 <0.05, so H2 is accepted. Earned Media and Social Media together have a positive and significant effect with an F value of 100,394 > F table 3.35 and a significance value of 0.000 < 0.05, so H3 is accepted.